BAGAIMANA PERAN SUMBER DAYA MANUSIA DALAM PENGEMBANGAN SEKTOR PARIWISATA? STUDI PADA PARIWISATA PANTAI DI KABUPATEN BLITAR - ahmad nizar yogatama (Journal of Global Business and Management Review, 2022)
This study wants to know the role of human resources in the development of the coastal tourism sector in Blitar district using a qualitative approach with phenomenological methods. The data analysis of Miles and Huberman models is data collection, data reduction, data display, and conclusion drawing/verification. The validity of the data used triangulation, namely source triangulation and technical triangulation. The results of this study indicate that the role of human resources is very important. Human resources must have competence in good coastal tourism governance. The role of human resources as stakeholders is technical implementer in policy making and practice, determining competitiveness, providing facilities, managing income, maintaining conduciveness, developing human resources, empowering communities, and improving and advancing the coastal tourism sector.